One-step synthesized antimicrobial peptide-functionalized gold nanoclusters for selective imaging and killing of pathogenic bacteria - Shen, Yunqiu; Zheng, Chaochuan; Wu, Qiaoli; Wu, Qilong; Jin, Ming; Jiang, Yayun; Huang, Fuyuan; Lou, Yongliang; Zheng, Laibao (Frontiers in Microbiology, 2022)
The development of multifunctional nanomaterials with bacteria imaging and killing is of great importance for the rapid diagnostic and timely treatment of bacterial infections. Herein, CWR11-AuNCs with high-intensity red fluorescence were successfully synthesized using a one-step method using CWR11 as a template through optimizing the ratio of CWR11 to HAuCl4, reaction time, pH and temperature. CWR11-AuNCs exhibited bacterial binding and selective imaging properties by fluorescence microscopy, which is expected to provide a feasible method for imaging and locating bacteria in complex environments in vivo. Besides, CWR11-AuNCs not only retained the antibacterial and bactericidal activities of CWR11, but also exhibited certain inhibitory or killing effects on Gram-negative，Gram-positive and biofilms. The MICs of CWR11-AuNCs against E. coli and S. aureus were 178 and 89 μg/mL respectively. For cytotoxicity, surprisingly, the cell viability of the CWR11-AuNCs treated group was 1.65 times that of the CWR11-treated group, and the low cytotoxicity exhibited by CWR11-AuNCs made them more promising for clinical applications.